Stacked Buckets: A Simple Solution to Solve Organic Kitchen Waste Problems - Untari, Dwi Suryanningdyah Heni; Kanafi, Rahmat; Sumaryati, Sumaryati (Prosiding Seminar, 2023)
The increased potential for accumulation of organic waste in society also results in increased potential for pollution, disease transmission, and the production of greenhouse gases. Kitchen organic waste is also a contributor to organic waste to the environment every day. The method currently most widely used to reduce organic waste is by utilizing the Black Soldier Fly (BSF) larvae (maggot). One way is to use the Stacked Buckets method. The Stacked BucketsMethod has been widely used at the household scale because it is easy to make, easy to use, and cheap